Hydraulic and drainage properties of Entisols and Inceptisols - SINGH, RAVENDER; BHARGAVA, G P (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1989-92 to evaluate the hydraulic and drainage characteristics of the soils of right-bank canal-command area of Mahi river in Gujarat. The soils of the command comprise Vertic Halaquept, Typic Halaquept, Typic Ustochrept, Fluventic Ustochrept, Vertic Ustochrept, Typic Ustorthent and Fluventic Ustorthents. The soils varied widely in their hydraulic and drainage properties. The highest saturated hydraulic conductivity (36.4 cm/day) was found in Typic Ustortnents and lowest (2.2 cm/day) in Vertic Halaquept, Critical water-table depth, when the upward flux was reduced to 0.1 cm/day, was 142, 164, 204,178,162,150,cm respectively in Vertic Halaquept, typic Halquenpt, Typic Ustochrept,Â Fluventic Ustochrept, Vertic Ustochrept, Typic Ustorthent and Fluventic Ustorthent under bare soil condition, The salinity hazards were in the order: Typic Ustochrept < Fluventic Ustochrept < Vertic Ustochrept < Typic Halaquept < Fluventic Ustorthent < Vertic Halaquept and < Typic Ustorthent. The chances of salinization were more in medium-textured soils than in fine- and coarse-textured ones. The highest maximum drainable porosity (0.117 cm3/cm3) was observed in Typic Ustorthent and lowest (0.070 cm3/cm3) in Vertic Halaquept Under natural condition of drainage, Typic Ustorthent and fluventic Ustorthent gave more water per unit fall of water-table, followed by Typic Ustochrept and Fluventic Ustochrept; whereas Vertic Halaquept, Typic Halaquept and Vertic Ustochrept gave less water.